2021
DOI: 10.1080/10408398.2021.1931806
|View full text |Cite
|
Sign up to set email alerts
|

New applications of advanced instrumental techniques for the characterization of food allergenic proteins

Abstract: Current approaches based on electrophoretic, chromatographic or immunochemical principles have allowed characterizing multiple allergens, mapping their epitopes, studying their mechanisms of action, developing detection and diagnostic methods and therapeutic strategies for the food and pharmaceutical industry. However, some of the common structural features related to the allergenic potential of food proteins remain unknown, or the pathological mechanism of food allergy is not yet fully understood. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 162 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…A recent review has summarized the many instrumental techniques applied in several areas of the food allergy field [ 47 ]. Nonetheless, specific surface plasmon resonance (SPR) sensors have been just developed to detect casein and β-LG [ 48 ], and its potential application to human milk is undeniable.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review has summarized the many instrumental techniques applied in several areas of the food allergy field [ 47 ]. Nonetheless, specific surface plasmon resonance (SPR) sensors have been just developed to detect casein and β-LG [ 48 ], and its potential application to human milk is undeniable.…”
Section: Resultsmentioning
confidence: 99%
“…The mode of food antigen consumption may alter the allergenicity of food antigens (23,24). In many studies, the type of cooked food antigen is not taken into consideration when assessing the tolerogenicity of the antigen.…”
Section: Kinetics Of Food Antigens In Breast Milk and Mode Of Antigen...mentioning
confidence: 99%
“…Park et al (25) showed that both roasted and raw peanuts had the same allergenic components; however, the processing of peanuts influences the allergenicity of peanut proteins. Specifically, the boiling of peanuts was found to decrease their allergenicity through the loss of low-molecular-weight allergens into water (26), while the roasting of peanuts was found to increase their allergenicity through the formation of neoepitopes of the main peanut allergens Ara h1 and Ara h2 (23). Therefore, it is clear that not only the mode of cooking but also food matrix interactions play a role in the allergenicity of antigens.…”
Section: Kinetics Of Food Antigens In Breast Milk and Mode Of Antigen...mentioning
confidence: 99%
“…Other analytical technologies are under development, but with scarce commercial presence. These include surface plasmon resonance (SPR) [ 127 , 128 , 129 ] electrochemical affinity biosensors [ 130 ]; the use of MIPs [ 131 ], biosensors, and nanoparticles, such as gold, carbon, and graphene [ 132 ]; and fluorescence-based methodologies [ 133 ]. The use of biosensors is an appealing alternative to instrumental analysis in food control, although there are currently few, if any, commercial applications for allergen control.…”
Section: Food Allergensmentioning
confidence: 99%